The Transformation of Halal Certification Regulations in Indonesia - Ibrahim, Muhammad Yusuf; Fauzi, Unang; Fadillah, Nurul; Satifa, Siti Annisa (Universitas Siliwangi, 2023)
Introduction to The Problem: Prior to the formation of BPJPH, LPPOM-MUI had a central role in supervising and providing halal certification. However, as time goes by, demands for halal certification regulations are increasingly complex and dynamic. Therefore, the government established BPJPH as the new authority responsible for the regulation of halal certification.Purpose/Objective Study: This study aims to investigate and analyze the development of halal regulations in Indonesia from the establishment of LPPOM-MUI to the formation of BPJPH. The focus of this research is to understand policy changes, the transition process, and the impact of this transition on halal certification in Indonesia.Design/Methodology/Approach: This study uses descriptive analysis methods and historical approaches to trace the development of halal regulations in Indonesia. The data was obtained through a review of official documents, policies, regulations, and related literature.Findings: The results of this study reveal a significant evolution in halal regulations in Indonesia. Initially, the LPPOM-MUI was responsible for halal certification, but later, the Indonesian government established BPJPH as an autonomous body tasked with managing the halal product assurance system. This transition has an impact on various aspects, including the process of certification, accreditation, and supervision.